Mesto ponoči - Drozg, Vladimir (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2016)
This paper focuses on the city at night. The distinctive aspect of the discussed topic is the time dimension of spaces and areas - places that "live" at night. The night has economic, cultural, social and formal elements; and it is these elements that underpin how we see and come to know the city at night. A range of topics have been explored: places of retailing and consumption, workplaces, places of entertainment, places that embody the night image of the city and places of socially unacceptable, delinquent behaviour. In the empirical part, we examined the city of Maribor, Slovenia.
Keywords: Maribor; mesta; naselja; Slovenia; Slovenija; urbana geografija